The Regulation of Phosphorus Release by Penicillium chrysogenum in Different Phosphate via the TCA Cycle and Mycelial Morphology - Wang, Liyan; Tian, Da; Zhang, Xiaoru; Han, Mingxue; Cheng, Xiaohui; Ye, Xinxin; Zhang, Chaochun; Gao, Hongjian; Li, Zhen (The journal of microbiology, 2023)
Phosphate-solubilizing fungi (PSF) efficiently dissolve insoluble phosphates through the production of organic acids. This study investigates the mechanisms of organic acid secretion by PSF, specifically Penicillium chrysogenum , under tricalcium phosphate (Ca 3 (PO 4 ) 2 , Ca–P) and ferric phosphate (FePO 4 , Fe–P) conditions. Penicillium chrysogenum exhibited higher phosphorus (P) release efficiency from Ca-P (693.6 mg/L) than from Fe–P (162.6 mg/L). However, Fe–P significantly enhanced oxalic acid (1193.7 mg/L) and citric acid (227.7 mg/L) production by Penicillium chrysogenum compared with Ca–P (905.7 and 3.5 mg/L, respectively). The presence of Fe–P upregulated the expression of genes and activity of enzymes related to the tricarboxylic acid cycle, including pyruvate dehydrogenase and citrate synthase. Additionally, Fe–P upregulated the expression of chitinase and endoglucanase genes, inducing a transformation of Penicillium chrysogenum mycelial morphology from pellet to filamentous. The filamentous morphology exhibited higher efficiency in oxalic acid secretion and P release from Fe–P and Ca–P. Compared with pellet morphology, filamentous morphology enhanced P release capacity by > 40% and > 18% in Ca–P and Fe–P, respectively. This study explored the strategies employed by PSF to improve the dissolution of different insoluble phosphates.